Related-key cryptanalysis of perspective symmetric block cipher - Oliynykov, R.; Kaidalov, D. (ХНУРЭ, 2014)
Symmetric block ciphers are among the most widely used cryptographic primitives. In addition to providing privacy via encryption, block ciphers are used as basic components in the construction of hash functions, message authentication codes, pseudorandom number generators as part of various cryptographic protocols etc. One of the most popular block ciphers nowadays is AES (Advanced Encryption Standard), which is used as a standard of symmetric encryption in many countries of the world. Several years ago a theoretical attack against the AES key-expansion algorithm was suggested, and complexity of this attack turned out to be significantly lower compared to brute force search. This paper considers the method of estimating encryption algorithm security against related-key attacks, and its application to the perspective block cipher, which is a candidate to the block encryption standard in Ukraine.
Keywords: block cipher; cryptanalysis; related key attack